A Rising Cancer Prevention Target of RSK2 in Human Skin Cancer - Narayanasamy, Arul; Cho, Yong-Yeon (Frontiers in Oncology, 2013)
RSK2 is a p90 ribosomal S6 kinase family (p90RSK) member regulating cell proliferation and transformation induced by tumor promoters such as epithelial growth factor (EGF) and 12-O-tetradecanoylphorbol-13-acetate. This family of p90RSK has classified as a serine/threonine kinase that respond to many growth factors, peptide hormones, neurotransmitters, and environmental stresses such as ultraviolet (UV) light. Our recent study demonstrates that RSK2 plays a key role in human skin cancer development. Activation of RSK2 by EGF and UV through extracellular-activated protein kinases signaling pathway induces cell cycle progression, cell proliferation, and anchorage-independent cell transformation. Moreover, knockdown of RSK2 by si-RNA or sh-RNA abrogates cell proliferation and cell transformation of non-malignant human skin keratinocyte, and colony growth of malignant melanoma (MM) cells in soft agar. Importantly, activated and total RSK2 protein levels are highly detected in human skin cancer tissues including squamous cell carcinoma, basal-cell carcinoma, and MM. Kaempferol and eriodictyol are natural substances to inhibit kinase activity of the RSK2 N-terminal kinase domain, which is a critical kinase domain to transduce their activation signals to the substrates by phosphorylation. In this review, we discuss the role of RSK2 in skin cancer, particularly in activation of signaling pathways and potent natural substances to target RSK2 as chemopreventive and therapeutic agents.